The evolutionary path of the kyrgyz press, which arose in parallel with statehood (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In the article, there is a historical analysis of the formation and evolution of the Kyrgyz press, which began with the establishment of the Kyrgyz Republic as a republic. It is noted that the press played a special role at the beginning of statehood. Because it is impossible to imagine the institutionalization of the state of the USSR, the formation and spread of ideological trends. The newspaper, as the earliest form of mass media, was considered the main means of modernization in its time. It is emphasized that the press played a big role in solving the problem of liquidation of illiteracy on the path of development of the republic that died only.
Keywords: press, word, information, information policy, foreign policy, domestic policy, printing, demand, region, state, statehood, Kyrgyz language, Russian language, country, journal, version, policy, district, region, article, political process, request, request, district committee, republic, Kyrgyz language, Russian language, collegium, council